Un défi majeur des villes indiennes : l’accès à un logement convenable - Véronique Dupont (Bulletin de l’Association de Géographes Français)
Indian cities are faced with an acute shortage in decent housing, which points to the double challenge of squatter settlement and slums, and forced evictions. The main strategies regarding squatter settlements, which comprise the provision of basic services, upgrading of housing conditions, relocation on alternative sites, and rehousing, addressed mainly the symptoms of housing poverty. But on the other hand, the many forced evictions without adequate rehabilitation programme have generated processes of exclusion and impoverishment for the evicted families. The debates about the role of the market in housing policies and rehousing programmes underline the divergences of views between those defending a neo-liberal agenda and those stressing the state responsibilities towards the weakest sections. The complexity of slum-related issues comes from the necessity to provide answers in the short and long-term. Different types of barriers to a better integration of the slum dwellers’ rights persist; in the Indian context, some are notably institutional, and other cultural and social.